2003
DOI: 10.1108/08876040310467934
|View full text |Cite
|
Sign up to set email alerts
|

An empirical examination of factors influencing the internationalization of service firms

Abstract: The internationalization of service firms is expanding dramatically, fueled by recent technological innovations and reductions of trade barriers. Drawing upon Dunning’s eclectic theory, firm‐ and location‐specific factors which have been found to be antecedents of internationalization of manufacturing firms are extended to determine their applicability to the internationalization of service firms. The hypotheses are empirically examined through a survey of 228 business‐to‐business service firms. Findings indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
138
0
10

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(153 citation statements)
references
References 67 publications
5
138
0
10
Order By: Relevance
“…Perceptions vary as to what constitutes a small, medium or large firm. The majority of the literature is derived from USA studies where definitions of size differ from the United Kingdom, Europe and elsewhere [23,24]. The transferability of findings and replicability of studies is therefore difficult to achieve, given these differences.…”
Section: Internationalisation and Firm Sizementioning
confidence: 99%
“…Perceptions vary as to what constitutes a small, medium or large firm. The majority of the literature is derived from USA studies where definitions of size differ from the United Kingdom, Europe and elsewhere [23,24]. The transferability of findings and replicability of studies is therefore difficult to achieve, given these differences.…”
Section: Internationalisation and Firm Sizementioning
confidence: 99%
“…Scholars agree that human capital is a multidimensional construct, but at the same time they differ on the dimensionality aspect. For example, previous studies have identified several human capital aspects such as attitudes (Javalgi, Griffith & White 2003), national diversity [attitude] (Caligiuri, Lazarova & Zehetbauer 2004), and experience (Seleim, Ashour & Bontis 2007). Nevertheless, these studies seem to be fragmented.…”
Section: Human Capitalmentioning
confidence: 99%
“…The cluster sublevel includes compact localization of manufacturing and services [18], internationalization of experience and technology, removal of barriers for entry into foreign markets [19,20], development of interorganizational relationships within the cluster, and special combination of infrastructural conditions [21]. The regional sublevel includes development of commercial, financial, and banking networks [22]; quality of key institutions in the region (namely, the protection of property rights, rule of law, level of business regulation, export policy [23]), urbanization factor, and maturity of urban agglomerations [24,13,14].…”
Section: Theory and Methodology Of The Studymentioning
confidence: 99%